1997
DOI: 10.4319/lo.1997.42.3.0461
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of iron and molybdenum in restricting phytoplankton biomass in high phosphorus saline lakes

Abstract: Eleven prairie saline (conductivity 1.8-58.8 mS cm-') lakes were examined over the 1994 growing season to determine what salinity-related factor or factors were responsible for controlling phytoplankton standing crops. The study lakes were characterized by high total P (0.15-24.2 mg liter-'), total N (3.75-12.35 mg liter-'), total Fe (55-2,800 p,g liter-'), dissolved organic C (40-195 mg liter-l), pH and alkalinity, but comparatively low (usually cl00 kg liter-') dissolved inorganic N. Chlorophyll a (Chl a) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 31 publications
2
40
0
Order By: Relevance
“…The absence of ambient levels of phosphate, the C:P ratio in particulate organic material, APA, and turnover times of phosphate were used for characterization of the phosphate limitation of plankton in various ecosystems (Graneli et al 1990, Fisher et al 1992, Thingstad et al 1993, Cotner et al 1997, Evans & Prepas 1997, Robarts et al 1998. Our investigations showed that the estimated time of phosphate limitation varied with the parameter used.…”
Section: Discussionmentioning
confidence: 89%
“…The absence of ambient levels of phosphate, the C:P ratio in particulate organic material, APA, and turnover times of phosphate were used for characterization of the phosphate limitation of plankton in various ecosystems (Graneli et al 1990, Fisher et al 1992, Thingstad et al 1993, Cotner et al 1997, Evans & Prepas 1997, Robarts et al 1998. Our investigations showed that the estimated time of phosphate limitation varied with the parameter used.…”
Section: Discussionmentioning
confidence: 89%
“…Tahoe (Chang et al 1992), and iron has been shown to restrict phytoplankton growth in high phosphorous saline lakes (Evans and Prepas 1997) and in hard-water calcareous lakes (Schelske 1962;Schelske et al 1962;Wetzel 1965).…”
mentioning
confidence: 99%
“…Iron has the potential to control the growth and composition of phytoplankton communities (Murphy et al 1983;Chang et al 1992;Pollingher et al 1995;Evans & Prepas 1997;Sunda & Huntsman 1997;Hyenstrand et al 1999;Schmidt & Hutchins 1999;Twiss et al 2000;Shaked et al 2004;Noiri et al 2005). This study demonstrated that the secretion from C. aciculare showed some patterns of selectivity in its effect on phytoplankton growth.…”
Section: Discussionmentioning
confidence: 99%
“…Iron limitation in freshwater is suggested to occur mainly via complexation of iron by organic matter (Imai 1999) and sulfide clusters (Rozan et al 2000). Phytoplankton has been shown to be limited by low availability of iron in hard-water lakes and saline lakes (Schelske 1962;Schelske et al 1962;Wetzel 1966;Evans & Prepas 1997). To survive under low iron availability conditions, many eukaryotic phytoplankton appear to acquire iron in a manner similar to 'strategy I' (Römheld 1987) for higher plants, in which iron limitation leads to an increase in plasma membrane ferric chelate reductase activity (Weger et al 2002).…”
Section: Introductionmentioning
confidence: 99%